Hubungan antara investasi asing langsung tehadap indeks harga perdagangan besar di Indonesia: Pendekatan model persamaan simultan - Lubis, Najma Azhira; Rangkuty, Dewi Mahrani; Efendi, Bakhtiar; Sari, Wahyu Indah (Nur Science Institute, 2025)
This study was conducted to examine the relationship between Foreign Direct Investment and the Wholesale Trade Price Index in Indonesia, and assess how export-import, Gross Domestic Product, import duties, and export tariffs also affect the dynamics of the relationship. Using a simultaneous equation model approach and the Two Stage Least Squares (TSLS) estimation method, this study utilizes time series data from 2007 to 2024. The results of the analysis show that the Wholesale Price Index has a significant negative impact on Foreign Direct Investment. At the same time, the influence of Export-Import and Export-Import_LAG1 on Foreign Direct Investment is not proven to be significant. On the other hand, the variables of Gross Domestic Product, import duties, export tariffs, and Foreign Direct Investment together have a significant influence on Export-Import. The value of the determination coefficient in the Export-Import model indicates a higher explanatory power than the Foreign Direct Investment model. These findings confirm that the stability of major trade prices and the strengthening of macroeconomic policies are indispensable to attracting foreign investment and boosting international trade activities.